Cybervictimization and depression among Malaysian adolescents: Sense of coherence as a moderator - Tee, Xiang Yi (2023)
Adolescents are increasingly using electronic devices, and this could increase the risk of cybervictimization. Cybervictimization was found to be associated with depression. Nonetheless, studies that used the Salutogenic Model of Health supported the moderating effect of sense of coherence in this association. Since no study has been conducted to access the moderating effect of sense of coherence between cybervictimization and depression in Malaysia, this study aims to investigate the association between cybervictimization and depression, as well as to investigate the moderating role of sense of coherence in this association among adolescent cybervictims. The final sample comprised 357 participants (age M = 14.34, SD = 0.86) who were recruited using purposive sampling in secondary schools located in Peninsular Malaysia and East Malaysia. Data was collected via paper-and-pencil questionnaires and online questionnaires. The measurements used were the European Cyberbullying Intervention Project Questionnaire, Sense of Coherence scale, and Short Mood and Feelings Questionnaire. From the path model, cybervictimization was positively associated with depression. Besides, moderation analysis indicated that sense of coherence was a significant moderator in the relationship between cybervictimization and depression. When sense of coherence was low, increased severity of cybervictimization was linked with increased depression. However, the strength of this association weakened when sense of coherence was high. In overall, the results contributed to raising awareness among authorities, parents, and adolescents to promote sense of coherence in prevention programs, as well as iv filling in the gaps regarding the moderating role of sense of coherence in the cybervictimization context among Malaysian adolescents